Integrated quality management model based on TQM, LM, EMS and ENMS for Malaysian automotive company / Argustina Zainuddin - Zainuddin, Argustina (2020)
An integrated management system (IMS) is integrated in all the systems and process into one complete framework, enabling an organization to work as a single unit in achieving the organization target and goals. In Malaysia, local manufacturing company usually adopted three quality systems such as Total Quality Management (TQM), Lean Manufacturing (LM) and Environmental Management System (EMS). The implementation of three management systems makes the organization very difficult to liaise with the objective because there are of a lot of documentation that is not being standardized. The objective of having all the management system is supposedly to make the organization to transform to become more competitive and sustainable organization. This study is a continuation from previous study and additional on Energy Management system (EnMS) to identify common parameters within four systems with a view of formulating a valid Integrated Quality Management Model applicable to the automotive industry to enhance their quality management endeavors. The study looks into quality management parameters, leadership, human resource, operation control, supplier organization and customer management. The study is implementing 30 active automotive companies MAJAICO and non MAJAICO participants in Klang Valley, Malaysia. The proposal is to integrate the framework model which is developed based on the responses of the survey. It also considering the impact of five common practices to financial and non-financial performance measurement indicators (PMIs) using SPSS. There were one company selected and two service centers for case study assessment. The data was analyzed to evaluate the percentage of the implementation and to determine the level of the practices which would be contributed to the establishment of Integrated Quality Management Model based on TQM, LM, EMS and EnMS in Malaysian Automotive companies which would develop a new framework model of integrated quality management system. The result from the case study assessment show that the awareness and knowledge about the energy management system is still not up to expectation more over lack of management aware and team focus for this IMS is not discuss up to management level. When explanation on the benefit of it make the company interested to implement however the readiness of it still need more time. The integrated management system for all quality system is new for all the company, the knowledge is given but the implementation still on hold up to management decision. The study suggests to extend more population not only in MAJAICO company but all selected automotive company in Malaysia. This will show more result and variant on the solution and recommendation. The study also needs to start increase announcement on benefit, improvement of integrated management system to the organization structure, resources and procedures that support the planning, monitoring, quality control, cost effective, energy efficiency and other activities of an organization. Lastly, the new framework can be proposed for implementation to the automotive industry in Malaysia.